(3OjhGf GHf OQGL GdbSWdjs - (3CHhYeQ CMeO Hf eMeO Hf GdYGU Hf OQGL GdbSWdj GdCfOdSj,J (B421 (3g` s
(3ChdgG (B:s
(3eHJhQ jHOC CKfGA bUjOI dGejI eVeheI Chd eG ajgG(B: (3ceG QaY GdBd GdghGOL HGdVMi ZOGI ESJbdJ HGdNdjW Mehd s
(3BNQgG (B:s
(3eHJhQ CjVkG, hBNQ eG ajg(B: (3hbGd jeOM Ydj Hf MehO QMege Gddg JYGdi ef MedI QSGdI s
(3GdOjhGf ZjQ eQJH Ydi GdbhGajs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B114s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B103 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B766s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs